Prevalence, demographics, and psychological associations of sleep disruption in patients with cancer: University of Rochester Cancer Center-Community Clinical Oncology Program - Palesh, Oxana G; Roscoe, Joseph A; Mustian, Karen M; Roth, Thomas; Savard, Josée; Ancoli-Israel, Sonia; Heckler, Charles; Purnell, Jason Q; Janelsins, Michelle C; Morrow, Gary R (Journal of clinical oncology, 2010)
Sleep disruption is prevalent in patients with cancer and survivors, but the prevalence of insomnia, a distressing sleep disorder, in these populations has yet to be determined in large-scale studies. A total of 823 patients with cancer receiving chemotherapy (mean age, 58 years; 597 female patients) reported on sleep difficulties in a prospective study. During day 7 of cycle 1 of chemotherapy, 36.6% (n = 301) of the patients with cancer reported insomnia symptoms, and 43% (n = 362) met the diagnostic criteria for insomnia syndrome. Patients with cancer younger than 58 years were significantly more likely to experience either symptoms of insomnia or insomnia syndrome (chi(2) = 13.6; P = .0002). Patients with breast cancer had the highest number of overall insomnia complaints. A significant positive association was found between symptoms of insomnia during cycles 1 and 2 of chemotherapy (phi = .62, P < .0001), showing persistence of insomnia during the first two cycles of chemotherapy. Sixty percent of the patient sample reported that their insomnia symptoms remained unchanged from cycle 1 to cycle 2. Those with insomnia complaints had significantly more depression and fatigue than good sleepers (all P < .0001). The proportions of patients with cancer in this sample reporting symptoms of insomnia and meeting diagnostic criteria for insomnia syndrome during chemotherapy are approximately three times higher than the proportions reported in the general population. Insomnia complaints persist throughout the second chemotherapy cycle for the majority of patients with cancer in this study. Insomnia is prevalent, underrecognized, undermanaged, and understudied among patients with cancer receiving chemotherapy.